Micro-graphite particles accelerate denitrification in biological treatment systems. (July 2020) - Li, Junzhang; Peng, Zhaozhou; Hu, Ruiyang; Gao, Kaiyuan; Shen, Chen; Liu, Shouxin; Liu, Runjing
Graphical abstract: Highlights: Low-dose MGP accelerates denitrification in synthetic and industrial wastewater. MGP can improve the proportion of Paracoccus in a sample. MGP can enhance the abundance of the nirS gene. MGP has hormesis effects on denitrifying bacteria. Abstract: Accelerated denitrification is an essential problem in the biological treatment of nitrogenous wastewater. In this study, we report that denitrification is accelerated by micro-graphite particles (MGPs). The denitrification rate was increased by 83.4% or 11.1% in synthetic (with 0.16 g/L MGPs) or industrial nitrogenous wastewater (with 0.12 g/L MGP), respectively. The mechanism was revealed via a quantitative polymerase chain reaction (q-PCR), high-throughput sequencing, and scanning electron microscopy (SEM). The abundance of denitrifying bacteria Paracoccus in the sludge was increased by micro-graphite particles. The number of denitrifying bacteria with the nirS gene was increased significantly (75.6%). To the best of our knowledge, this is the first report that MGP could enhance denitrification via the sludge. MGP can denitrify in industrial applications.